1997
DOI: 10.1111/j.1558-5646.1997.tb03954.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Parasites From Their Hosts: A Case Study in the Parasitic Red Algae

Abstract: Abstract.-Morphological similarities of many parasites and their hosts have led to speculation that some groups of plant, animal, fungal, and algal parasites may have evolved directly from their hosts. These parasites, which have been termed adelphoparasites in the botanical literature, and more recently, agastoparasites in the insect literature, may evolve monophyletically from one host and radiate secondarily to other hosts or, these parasites may arise polyphyletically, each arising from its own host. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 19 publications
6
55
0
1
Order By: Relevance
“…This mode of radiation has been documented in various parasitic taxa, such as mistletoes (64), red algae (65), and gall wasps (66), and seems plausible also in bumblebee (35) and paper wasp inquilines (37). Alternatively, ''karavajevi'' may have increased its host array concurrently with speciation events in its original host lineage.…”
Section: Discussionmentioning
confidence: 65%
“…This mode of radiation has been documented in various parasitic taxa, such as mistletoes (64), red algae (65), and gall wasps (66), and seems plausible also in bumblebee (35) and paper wasp inquilines (37). Alternatively, ''karavajevi'' may have increased its host array concurrently with speciation events in its original host lineage.…”
Section: Discussionmentioning
confidence: 65%
“…Due to the morphological and genetic similarity of red algal parasite and host, it has been suggested that the parasite evolved from its host (Goff et al 1997, Blouin and Lane 2012, Ng et al 2013. For example, the parasite Congracilaria babae Yamamoto is more closely related to its host Gracilaria salicornia (C. Agardh) Dawson than the…”
Section: Distribution Of the Rhodophyllis Parasitementioning
confidence: 99%
“…Red algal parasites are common on other red algae and have been described from several orders within the Florideophyceae (Goff 1982), a few molecular-based phylogenetic studies have focused on a handful of species (Goff et al 1997, Zuccarello et al 2004, Ng et al 2013, with new species still being described (Kim and Cho 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ronquist 1994;Ward 1996;Lowe & Crozier 1997)). These phenomena are not conned to hymenopterans: Emery's rule also applies to groups of fungi, red algae and perhaps mistletoe (Goff et al (1997) and references therein). Three sequences of events have been suggested to lead to either strict or loose conformity with Emery's rule.…”
Section: Introductionmentioning
confidence: 99%